Transformation of chemically fine tuned zeolite A precursor into dense lithium aluminosilicates - a comprehensive phase evolution and sintering study - Selvaraj, Kaliaperumal (Microporous and Mesoporous Materials, 2010)
Beyond their conventional revelation as catalysts, zeolites are being perceived as more challenging materials for modern applications. Thermal recrystallization of zeolite precursors is an efficient method for the preparation of dense aluminosilicate ceramics. However, factors viz., nature of the precursor and the way of firing it etc., influence the product quality. The present report is a systematic and detailed account of a phase transformation of Li modified zeolite A precursor using powder X-ray diffraction (PXRD), thermogravimetry (TG), differential thermal analysis (DTA), scanning electron micrographs (SEM), atomic absorption spectroscopy (MS), energy dispersive X-ray (EDX) and density measurement techniques. It involves an amorphisation followed by a recrystallization into lithium aluminosilicate (LAS). A comprehensive correlation of PXRD, TG/DTA, SEM, EDX and density data explains the complexity of high temperature phase transition (25-1200 degrees C). A qualitative phase analysis revealed the mediation of formation of LAS ceramic, beta-spodumene by few satellite transitions of SiO(2). (C) 2010 Elsevier Inc. All rights reserved.
Keywords: LAS silicate; Phase evolution; Phase transformation; Powder XRD; zeolite

Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability